Mammalian Period represses and de-represses transcription by displacing CLOCK–BMAL1 from promoters in a Cryptochrome-dependent manner - Chiou, Yi-Ying; Yang, Yanyan; Rashid, Naim; Ye, Rui; Selby, Christopher P.; Sancar, Aziz (Proceedings of the National Academy of Sciences - PNAS, 2016)
The mammalian circadian clock is based on a transcription-translation feedback loop (TTFL) consolidated by secondary loops. In the primary TTFL, the circadian locomotor output cycles kaput (CLOCK)–brain and muscle Arnt-like protein-1 (BMAL1) heterodimer acts as the transcriptional activator, and Cryptochrome (CRY) and Period (PER) proteins function as repressors. PER represses by displacing CLOCK–BMAL1 from promoters in a CRY-dependent manner. Interestingly, genes with complex promoters may either be repressed or de-repressed by PER, depending on the particular promoter regulatory elements. Here, using mouse cell lines with defined knockout mutations in clock genes, RNA-seq, ChIP-seq, and reporter gene assays coupled with measurements of DNA–protein interactions in nuclear extracts, we elucidate the dual functions of PER as repressor and de-repressor in a context-dependent manner.